Clinical Analysis of Risk Factors of Postoperative Psychiatric Disorders in Patients With Adult Craniopharyngioma - Zhao, Rui; Lu, Pengwei; Fan, Yanzhu; Li, Chuzhong; Liu, Chunhui; Zhao, Peng; Cao, Lei; Gao, Hongwei; Gui, Songbai (Frontiers in Neurology, 2021)
Objective: To analyze the risk factors relative to postoperative psychiatric disorders in adult patients with craniopharyngioma. Methods: A retrospective case-control study design was used in this study. The Neuropsychiatric Inventory–Questionnaire (NPI-Q) assessment tool was used to assess psychiatric disorders in postoperative patients with craniopharyngioma at Beijing Tiantan Hospital from January 2018 to December 2020. The relationship between the psychiatric disorders and basic demographic data as well as several risk factors, such as the tumor characteristics (tumor location, tumor size, pathological finding of the tumor, etc.) and treatment-related factors (the extent of the resection), were analyzed. Results: A total of 173 patients were included in this study. The prevalence of psychiatric disorders was 14.5% among adult craniopharyngioma patients. Irritability represented the most common type of psychological symptom (64%, n = 16), followed by agitation (36%, n = 9), and delusions (28%, n = 7). The risk factors relative to postoperative psychiatric disorders that were identified were a tumor volume larger than 7 cm3 (HR = 3.292, P = 0.042), tumor location (P = 0.003), hypothalamic invasion (HR = 9.766, P = 0.036), and gross-total resection (HR = 0.085, P = 0.042). Conclusion: Neurocognitive assessment and intervention before and after surgery are important in patients with larger tumors, invading the third ventricle, and tumors with hypothalamic invasion. Prediction of these risk factors is essential for the treatment.